2007
DOI: 10.1111/j.1365-2966.2007.12214.x
|View full text |Cite
|
Sign up to set email alerts
|

Reionization scenarios and the temperature of the intergalactic medium

Abstract: We examine the temperature structure of the intergalactic medium (IGM) due to the passage of individual ionization fronts using a radiative transfer (RT) code coupled to a particle‐mesh N‐body code. Multiple simulations were performed with different spectra of ionizing radiation: a power law (∝ ν−0.5), miniquasar, starburst, and a time‐varying spectrum that evolves from a starburst spectrum to a power law. The RT is sufficiently resolved in time and space to correctly model both the ionization state and the te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
2

Year Published

2007
2007
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 79 publications
(148 reference statements)
7
114
2
Order By: Relevance
“…This would boost the gas temperature, possibly by the required amount. The effects of heating by late He II reionization may be mimicked to some extent by boosting the He II heating rate ͑Bryan and , but the only fully satisfactory solution requires incorporating radiative transfer ͑Tittley and Meiksin, 2007͒. With the goal of developing a physical description for the origin of the Doppler parameter distribution, Hui and Rutledge ͑1999͒ introduced a semianalytic approach based on the growth of the density perturbations to derive a Doppler parameter distribution of the form…”
Section: Spectral Properties Of the Igmmentioning
confidence: 99%
See 1 more Smart Citation
“…This would boost the gas temperature, possibly by the required amount. The effects of heating by late He II reionization may be mimicked to some extent by boosting the He II heating rate ͑Bryan and , but the only fully satisfactory solution requires incorporating radiative transfer ͑Tittley and Meiksin, 2007͒. With the goal of developing a physical description for the origin of the Doppler parameter distribution, Hui and Rutledge ͑1999͒ introduced a semianalytic approach based on the growth of the density perturbations to derive a Doppler parameter distribution of the form…”
Section: Spectral Properties Of the Igmmentioning
confidence: 99%
“…Another exploits a polytropic relation between the gas density and temperature ͑Hui and Gnedin, 1997;Schaye et al, 1999͒, calibrated using numerical simulations. Both methods rely on numerical simulations that neglect the effect of reionization on the temperature of the underdense gas, which may be substantial ͑Abel and Bolton et al, 2004;Tittley and Meiksin, 2007͒ temperature jump and reduction in the polytropic index toward isothermality near z = 3.0. . Although any conclusion using these methods is subject to the accuracy of the modeling assumptions made, the possibility of measuring an unambiguous temperature jump in this redshift range merits further investigation.…”
Section: Spectral Properties Of the Igmmentioning
confidence: 99%
“…We ran reionization simulations using methods similar to Tittley & Meiksin (2007) but adapted to a point radiation source. The gas density is assumed to trace the dark matter in a 256 3 N-body simulation in a box with a comoving side of length 25 h À1 Mpc.…”
Section: He II Ionization Regionmentioning
confidence: 99%
“…There are several suggestions for a physical explanation of this correlation like self-shielding and shadowing effects (Maselli & Ferrara 2005;Tittley & Meiksin 2006) and the spatial distribution of QSOs as the sources of hard radiation (Bolton et al 2006). However, Fechner & Reimers (2007) suggested that part of the correlation might be due to the unjustified assumption that the line widths of the absorption features are dominated by purely turbulent broadening.…”
Section: Send Offprint Requests To: C Fechnermentioning
confidence: 99%
“…Theuns et al 2002a) and provides constraints on the nature of the reionizing sources (e.g. Tittley & Meiksin 2006). The usual approach to measure the temperature considers the Doppler parameter distribution of Lyα forest absorbers (e.g.…”
Section: Introductionmentioning
confidence: 99%